Treatment with recombinant tumor necrosis factor-related apoptosis-inducing ligand alleviates the severity of streptozotocin-induced diabetes. - Zauli, Giorgio; Toffoli, Barbara; di Iasio, Maria Grazia; Celeghini, Claudio; Fabris, Bruno; Secchiero, Paola (Diabetes, 2010)
OBJECTIVE: To evaluate the potential therapeutic effect of recombinant human tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) treatment in a model of type 1 diabetes. RESEARCH DESIGN AND METHODS: Recombinant TRAIL was added in vitro to primary human and mouse peripheral blood mononuclear cells (PBMCs) and isolated human islets to evaluate the expression of the immunoregulatory gene SOCS1. Diabetes was induced by five consecutive daily injections of low-concentration (50 mg/kg) streptozotocin (STZ) in C57 black mice (n = 24). A group of these mice (n = 12) was co-injected with recombinant TRAIL (20 microg/day) for 5 days, and the diabetic status (glycemia and body weight) was followed over time. After 6 weeks, circulating levels of insulin, TNF-alpha, and osteoprotegerin (OPG) were measured, and animals were killed to perform the histological analysis of the pancreas. RESULTS: The in vitro exposure of both PBMCs and human islets to recombinant TRAIL significantly upregulated the expression of SOCS1. With respect to STZ-treated animals, mice co-injected with STZ+TRAIL were characterized by 1) lower levels of hyperglycemia, 2) higher levels of body weight and insulinemia, 3) a partial preservation of pancreatic islets with normal morphology, and 4) a lower expression of both systemic (TNF-alpha and OPG) and pancreatic (vascular cell adhesion molecule [VCAM]-1) inflammatory markers. CONCLUSIONS: Overall, these data demonstrate that the administration of recombinant TRAIL ameliorates the severity of STZ-induced type 1 diabetes, and this effect was accompanied by the upregulation of SOCS1 expression.
Keywords: Animals; Cells, Cultured; Diabetes Mellitus, Experimental; Gene Expression; Humans; Islets of Langerhans; Leukocytes, Mononuclear; Mice; Recombinant Proteins; Suppressor of Cytokine Signaling Proteins; TNF-Related Apoptosis-Inducing Ligand